(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Considerazioni introduttive - 2. Minoranze religiose e costruzione della nazione - 3. Per una storia delle minoranze religiose. Religious minorities in Italy: a historical-religious perspective ABSTRACT: The history of religious minorities in unitary Italy has been deeply linked to the construction of the national state both in its formative phase (the Risorgimento) and in the period of liberal Italy. The responses ranged between a desire for integration, as in the Jewish case, and an occasional and missionary presence, as in the case of certain Evangelical communities. The Great War, first, the twenty years of Fascism, then, profoundly changed this situation, further marginalizing the religious minorities also as a consequence of the 1929 Concordat.